Traços otobiográficos na poesia lírica de Marcos Siscar - Oliveira, Maria Eduarda Cesar de (2023)
The present work aims to analyze the manifestation of some otobiographical traits in the poetic works of Marcos Siscar. We recognize these traces in Siscar's lyrics, through the analysis of the dialogue between the Brazilian poet and Jacques Derrida's theoretical assumptions. Our research focuses, more specifically, through the investigation of the presence of the quasi-concepts "proper name" and "signature", which, for this philosopher, are constituent elements of otobiography. We find this discussion in the works Otobiographies (1985), Margins of Philosophy (1991) and Paixões (1995). We selected these books because it is in them that the critic Siscar develops his interpretation of the otobiography, evidenced in his essays "Paixão ungrata" (2012) and "How to give reason to Jean Genet" (2012). In the present work, this theoretical framework contributes to the investigation of the presence of the "proper name" in the poems "Sabia?", "Galo" and "A Picture with a tear and perhaps a smile". Furthermore, we examine the concept of "signature" in the poems "São Paulo 1972" and "Spitting against the wind". Thus, we initially present Siscar's critical reading of the otobiography, and then we verify how these quasi-concepts are present in such lyrical texts.